Representing the problems of the thesis and dissertation process: A qualitative study - Ali Zarei; Mohammad Javadipour; Keyvan Salehi (Allameh Tabataba'i University Press, 2018)
The purpose of this study was to analyze the problems of the thesis implementation process and dissertations of the students of the Faculty of Psychology and Educational Sciences of Tehran University and to provide some solutions to the existing problems. The present study was conducted in the framework of qualitative approach with phenomenological method. The research field was the University of Tehran and the participants were 8 postgraduate students and postgraduate students of the Faculty of Psychology and Educational Sciences of the University of Tehran. Data were collected using in-depth semi-structured interviews. Data were analyzed using the George method in five steps. Research findings showed that graduate students' perceptions of students' problems in the process of their thesis and dissertation were divided into 7 general themes including student problems or individual factors (9 themes), professors' problems (10 themes), macro community problems (8 themes), Includes bureaucratic problems (8 sub-themes), problem selection (2 sub-themes), material problems (3 sub-themes) and implementation problems (2 sub-themes).